Effect of Adefovir Dipivoxil on the Inhibition of Osteogenic Differentiation of Mesenchymal Stem Cells and Osteoblasts - Ho PARK (Korean Journal of Clinical Laboratory Science, 2023)
Adefovir dipivoxil (ADV) is used for the treatment of hepatitis and acquired immunodeficiency syndrome, but long-term use can cause osteoporosis. In this study, the effect of ADV on the osteocyte maturation process was evaluated at the level of undifferentiated cells using mesenchymal stem cells (MSCs) and osteoblasts (MG63). First, MSCs and MG63 cells were treated with ADV at different concentrations, and then a Cell Counting Kit-8 analysis was performed to determine the effect on the proliferation of each cell. Additionally, crystal violet and Hoechst staining were performed for the morphological analysis of each cell and nucleus. To determine the cause of cell hypertrophy, the transforming growth factor-beta (TGF-β) expression was investigated, and alkaline phosphatase (ALP) staining and activity were measured to determine the degree of differentiation of the MSCs and MG63 cells into mature osteocytes. The results confirmed that the ADV increases the expression of TGF-β in MSCs and MG63 cells, causing cellular and nuclear hypertrophy, and can cause osteoporosis by inhibiting cell proliferation and affecting the differentiation of mature osteocytes. Therefore, it is believed that these results can be used as a basis for understanding the adverse effects of ADV at a cytological level in basic medicine and clinical research.